The Philosophy of Human Rights Based on the Views of Ayatullah Jawadi Àmuli - hamid Parsania (حکمت اسرا)
Human rights is composed of epistemological-ontological dimensions as well as non-epistemological ones. The former is composed of principles, sources, and fundamental or foundations of belief. Thesefoundations include ontological foundations, anthropological foundations, and epistemological foundations. The term “philosophy of human rights” can be used in one of two ways: The first is as a second-degree science which speaks to the relation and connection between human rights and its principles, sources, and foundations. Accordingly, the philosophy of human rights is part of the foundational methodological study of human rights. The second way that the term can be used is as a study of the sources, foundations and metaphysical beliefs of human rights. In other words, it pertains to its truth or error. In this sense, the philosophy of human rights would fall under metaphysics. This article begins by discussing the basic principles and foundational beliefs that are necessary in formulating a universal set of human rights. Thereafter, the ontological, anthropological, and epistemological foundations of the Islamic rights of man are discussed. The sources and foundations, which are extracted from those principles, are elaborated on. In conclusion, through a comparative process, the distinguishing features of Islamic human rights are mentioned in comparison to the Universal Declaration of Human Rights.